A PRODUCTION OF PERFORMING ART ONLINE VIDEO FOR 21ST CENTURY SKILLS, A CASE STUDY: FOLK PERFORMING ARTS OF COMMUNITY’S CULTURAL IDENTITIES IN UTTARADIT PROVINCE - Permudomsap, Wanisara; Wanwichai, Rawiwan; Inchan, Noppadol (Journal of MCU Nakhondhat, 2023)
The purpose of this research to 1) developing folk performing arts education media of three cultural identity communities in Uttaradit Province that meets the 80/80 effectiveness criterion to Mattayomsuksa 4 students 2) determining the effectiveness index of Mattayomsuksa 4 students after studies by folk performing arts education media of three cultural identity communities in Uttaradit Province 3) investigating to Mattayomsuksa 4 students satisfaction after studies by folk performing arts education media of three cultural identity communities in Uttaradit Province. The experiment utilized random sampling with 10 people from Mattayomsuksa 4 students in Uttaradit Daruni School, Uttaradit and 10 people from Mattayomsuksa 4 students in Bodindecha (Sing Singhaseni) School, Bangkok. The Instrument used were education media for folk performing arts in three cultural identity communities in Uttaradit Province, Article covered test, Performance assessment form. Data were collected and analyzed using Efficiency of education media for folk performing arts ( / ), The Effective Index: (E.I.), Mean, Percentage, Standard Deviation. The research findings present the development of education media for folk performing arts in three parts: part 1) Lanna culture - Song Long Nan performance, part 2) Lan Xang Culture-Tap Tao Show, and part 3) Central Thai Culture-Canary long drum dance performance. The content of the performing arts encompasses the performance’s history, style, dress, props, inheritance, dissemination, and tourist attractions with cultural identity. The analysis of Uttaradit Darunee School in Uttaradit Province showed an efficiency value of 84.0/87.5, an effectiveness index of 0.742, and a high level of learning satisfaction. Similarly, Bodindecha School in Bangkok Province demonstrated an efficiency value of 86.00/85.00, an effectiveness index of 0.659, and a very good level of learning satisfaction. Both schools met the efficiency and effectiveness criteria established for the research.